Performance of MPLS-based Virtual Private Networks and Classic Virtual Private Networks Using Advanced Metrics - Kennedy Okokpujie; Olamilekan Shobayo; Etinosa Noma-Osaghae; Okokpujie Imhade; Obinna Okoyeigbo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Multiprotocol Label Switching (MPLS) is effective in managing and utilizing available network bandwidth. It has advanced security features and a lower time delay. The existing literature has covered the performance of MPLS-based networks in relation to conventional Internet Protocol (IP) networks. But, too few literatures exist on the performance of MPLS-based Virtual Private Networks (VPN) in relation to traditional VPN networks. In this paper, a comparison is made between the effectiveness of the MPLS-VPN network and a classic VPN network using simulation studies done on OPNET®. The performance metrics used to carry out the comparison include; End to End Delay, Voice Packet Sent/Received and Label Switched Path’s Traffic. The simulation study was carried out with Voice over Internet Protocol (VoIP) as the test bed. The result of the study showed that MPLS-based VPN networks outperform classic VPN networks.